POLICY STRATEGIES FOR REDUCING CARBON EMISSIONS IN THE TRANSPORTATION SECTOR - Muhammad Syamil Fadlillah; Erma Suryani (STTAL POSTGRADUATE - INTERNATIONAL CONFERENCE, 2024)
This study uses system dynamics modeling to explore policy strategies for reducing carbon emissions in the transportation sector by adopting electric vehicles (EVs). It addresses global warming and climate change, aligning with the 13th Sustainable Development Goal on climate action. The research focuses on transitioning from fossilfuel-powered vehicles to EVs, with governments worldwide implementing incentives and tax benefits to promote this shift. The study develops a dynamic system model to assess both the economic and environmental impacts of EV adoption, considering international and national policy factors. By evaluating government incentives, infrastructure development, and public acceptance, the research aims to provide policy recommendations that optimize environmental and economic benefits, facilitating a smoother transition to EVs and contributing to sustainable development goals. Copyright © 2024 STTAL. - All rights reserved.